Strength Changes in Peat-Polymer Stabilization Process; An Introduction of New Material for Peat Condition - Mohd Razali, Siti Nooraiin; Zainorabidin, Adnan; Bakar, Ismail; Mohamad, Habib Musa (International Journal of Integrated Engineering, 2019)
Peat represent as an extreme form of soft soil that subjected to instability. In order to reduce the scarcity of land for construction purpose, it is necessary to stabilize a soft and weak foundation. The engineers commonly faced with the constraint of accessibility and stability problem when dealing with peat. This paper describes a study on peat stabilization to enhance its strength by using an organic polymer soil stabilizer. To identify the strength change for the stabilization of peat by using Vinyl Acetate - Acrylic Copolymer (VAAC), laboratory tests on unconfined compression test was performed for 1, 7, 14 and 28 days of curing periods. The additive that works as a binder material such as sand, lime and cement were used in this study. The effect of this additive on the strength gained based on percentage materials used is highlighted. The unconfined compression test results show that the peat soil gained higher strength due to the addition of 70% of VAAC at 14 days of curing periods. The addition of 30%, 50% and 70% binder into stabilized peat with 20% and 70% of VAAC were reduced the strength of VAAC-P.